The Relationship Between Body Mass Index and Family Support for COVID-19 Recovery in Self-Isolating Patients - Imani, Mutiara Nurul; Setiawan, M. Riza; Anggraeni, Nina (Universitas Nusa Cendana, 2023)
From July 2021 to March 2022, cases of COVID-19 were reported increasing every day. The SARS-CoV2 virus infects the human body via the ACE2 receptor, the expression level of ACE2 is highest in adipose tissue. This causes obese patients to show more severe symptoms of COVID-19. During the independent isolation period, patients really need help from other parties in order to be able to meet their needs, especially in terms of providing consumption and medicine as well as motivation to obtain recovery, especially from the closest people, namely the family. The general aim of this study is to describe the correlation between body mass index and family support for COVID-19 recovery in self-isolation patients. This research is an analytic observational study with a cross-sectional design and a sampling technique using simple random sampling. The research instrument used medical records and family support questionnaires. The data obtained were analyzed using bivariate analysis, namely the chi-square test. The results of the study explained that there was a significant relationship between body mass index and family support for COVID-19 recovery in self-isolated patients in the work area of the Brebes Health Center. COVID-19 patients who have an obese body mass index are advised to seek treatment at the hospital if they already have symptoms of COVID-19 in the moderate category. Families are advised to increase family support, especially when caring for COVID-19 patients who are carrying out independent isolation. It is hoped that the government can become an evaluation and input to better monitor the health of patients who are conducting independent isolation, especially patients who have an obese body mass index.